Digital Government Post-Reform in Indonesia: Normative Developments and Implementation by State Organizing Institutions - Setyawan, Yhannu; Erliyana, Anna; Makarim, Edmon; Sjarif, Fitriani Ahlan; Dewi, Lia Riesta; Sukma, Ahmad Novindri Aji (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
Digital development has had a positive impact on public services; however, it has also introduced various legal challenges. This study aims to examine the direction of policy, legal preparedness in Indonesia, and the participatory role of Indonesian society in the digital sphere, particularly in relation to the development and implementation of Digital Government in Indonesia since the post-1998 reform era. This research employs a normative legal methodology, focusing primarily on secondary legal sources.The analysis reveals that the implementation of Digital Government in Indonesia following the reform period remains hindered by sectoral egos, leading to a lack of integration among state institutions in enhancing public services through the Digital Government framework. The study concludes that there is an urgent need for the establishment of a dedicated law on Digital Government, as well as the creation of a specialized state institution responsible for regulating, implementing, and evaluating Digital Government initiatives in Indonesia. Such measures are essential to ensure that public services are delivered in an efficient, accountable, transparent, fast, accessible, and cost-effective manner.